Impact of Alcohol on Occupational Health and Safety in the Construction Industry at Workplaces with Scaffoldings - Marek Sawicki; Mariusz Szóstak (Applied Sciences, 2020)
The value, care, and customs of workers are essential in terms of occupational health and safety. The abuse of alcohol is widely regarded as a serious threat to the lives, health, and safety of employees. The aim of the research was to identify the main problems that are associated with alcohol abuse and consumption at work among employees in the construction industry, with particular emphasis on workstations where work is carried out on construction scaffoldings. Data for the analysis were obtained from two different sources. The first one was post-accident documentation on occupational accidents. The second one was surveys collected during the research project. This study confirmed that excessive and disproportionate alcohol consumption can be the cause of an accident, and consequently death at workplaces with scaffolding. Of 219 accident reports, 17.4% indicated alcohol as a contributing factor. Analysis of accident documentations shows that in cases where alcohol was indicated as a contributing factor in an accident, the alcohol was consumed during the workday. The results obtained on the basis of the conducted research were able to constitute a justification for the directions of preventive actions carried out in order to reduce the number of occupational accidents in the construction industry caused by alcohol.